Predicting the degradation behavior of magnesium alloys with a diffusion-based theoretical model and in vitro corrosion testing. Issue 7 (July 2019) - Shen, Zhenquan; Zhao, Ming; Bian, Dong; Shen, Danni; Zhou, Xiaochen; Liu, Jianing; Liu, Yang; Guo, Hui; Zheng, Yufeng
Abstract: Magnesium alloys have shown great potential for their use in the medical device field, due to the promising biodegradability. However, it remains a challenge to characterize the degradation behavior of the Mg alloys in a quantitative manner. As such, controlling the degradation rate of the Mg alloys as per our needs is still hard, which greatly limits the practical application of the Mg alloys as a degradable biomaterial. This paper discussed a numerical model developed based on the diffusion theory, which can capture the experimental degradation behavior of the Mg alloys precisely. The numerical model is then implemented into a finite element scheme, where the model is calibrated with the data from our previous studies on the corrosion of the as-cast Mg-1Ca and the as-rolled Mg-3Ge binary alloys. The degradation behavior of a pin implant is predicted using the calibrated model to demonstrate the model's capability. A standard flow is provided in a practical framework for obtaining the degradation behavior of any biomedical Mg alloys. This methodology was further verified via the comparison with enormous available experimental results. Lastly, the material parameters defined in this model were provided as a new kind of material property.